IB-Trajectory: Um Modelo Semântico para Representação de Trajetórias Baseadas em Itinerários - VIRGENS, Duílio Santa Bárbara das (2015)
With the decreasing cost of positioning technology and data communication, various technological solutions have been deployed in the public transport system. Virtually all major urban centers use GPS in buses and use this information to provide the instantaneous vehicle position. Despite the storage of all positions collected from vehicles are registered in the corporate database, applications that use information about the positioning of the vehicles are only interested in the real-time information, that is, offer services only at the operational level. For offering services and analyzes the strategic or tactical level, it is necessary processing and analysis of historical records of trajectories.This paper presented a conceptual model to represent trajectories vehicles moving along the road network and have an itinerary and a time scale to be followed. The aim is to facilitate the analysis and visualization of the trajectories of objects that perform this type of movement in order to identify patterns, discover anomalies, show deviant behavior, establish relationships with other phenomena and improve the general knowledge about this type of movement. The proposed model was applied as proof of concept, the analysis of trajectories of the public bus system mass transit. This model, however, can be used to analyze the behavior of vehicle logistics companies, delivery of goods, maintenance of infrastructure and equipment or any conditioned vehicle to carry out programmed paths.